Moral Reasoning According to Gender in Citizenship Education Learning - Khairul Huda; Muhammad Syauqi; Muhammad Farid Akbar; Rahmansyah Fadlul Al Karim Rambe (International Journal of Cultural and Social Science, 2024)
Moral is a measure of the good and bad of a person, both as a person and as a citizen, and a citizen.Meanwhile, moral education is education to make human children morally good and humane. This paperaims to provide an overview of instilling moral values in students through civic education and knowingthe definitions of moral, moral education and moral education in children. The research method used is touse a literature review research method or literature study which contains theoretical theories that arerelevant to research problems. The conclusion of this paper is that the moral prescription of students isnot only from class lessons, but in Citizenship Education lessons also participate in the moral ordering of students